20Gb/s WDM-OFDM-PON over 20-km single fiber uplink transmission using optical millimeter-wave signal seeding with rate adaptive bit-power loading - Kartiwa, Iwa; Jung, Sang-Min; Hong, Moon-Ki; Han, Sang-Kook (Optical fiber technology, 2013)
► Spectral-efficiency achieved using OFDM-based signal. ► Optical carrier suppression method with single laser to double the capacity. ► Single fiber loopback link with colorless ONU realized using RSOA. ► Optimizing the BER and data rate using rate adaptive bit-power loading algorithm. We experimentally demonstrate the use of millimeter-wave signal generation by optical carrier suppression (OCS) method using single-drive Mach–Zehnder modulator as a light sources seed for 20Gb/s WDM-OFDM-PON in 20-km single fiber loopback transmission based on cost-effective RSOA modulation. Practical discrete rate adaptive bit loading algorithm was employed in this colorless ONU system to maximize the achievable bit rate for an average bit error rate (BER) below 2×10−3.